In-vivo protein quality assessment of macerated African elemi pulp eaten as masticatories in Eastern Nigeria - Anyalogbu, E. A. A. (2021)
Processing improved feed utilization (FU), feed conversion ratio (FCR), protein efficiency ratio (PER) and, except at AE30, net protein utilization (NPU) and biological value (BV) of the rats. The PER was above 2.0 in all the rats sustained on test sample diets given the range 2.03 ± 0.23 to 2.28 ± 0.35. The fecal nitrogen (FN), carcass weight (CW), true digestibility (TD), and BV were statistically similar (p˃0.05) in rats fed both samples and reference diets with BV being above 70%. Relative to FN, TD, and BV, this statistical parity between animals on test and reference diets could suggest adequacy of the digestibility of the proteins of the sample diets and the similarities in their qualities.